Gambier for Diabetes: Comparison of the Antidiabetic Potency between Two Types of Extracts from Uncaria gambir (W. Hunter) Roxb. - Fajarwati, Indah; Solihin, Dedy Duryadi; Wresdiyati, Tutik (Jurnal Kefarmasian Indonesia, 2024)
Gambier is a dry extract obtained from both the leaves and twigs of the Uncaria gambir. It is an agricultural product produced by the local community through traditionally unique methods. The main objective of this study was to evaluate the antidiabetic potency of gambier. The study used two types of gambier, namely traditional aqueous gambier (TAG) from traditional extraction and maceration ethanol gambier (MEG) from maceration extraction. The phytochemical compound, alpha-glucosidase inhibition, and antioxidant activity were analyzed. Moreover, in vivo hypoglycemia activity study was carried out. The results showed that both TAG and MEG contained flavonoids, tannin, and triterpenoids, while saponins were detected in TAG and steroids in MEG only. Both TAG and MEG also contained quercetin and catechin which were higher in the TAG compared to the MEG. The DPPH scavenging activities of the TAG and MEG, measured in IC50 values, were 15.40 ± 0.21 μg/ml and 12.25 ± 0.04 μg/ml, respectively. The IC50 values of the alpha-glucosidase inhibition of TAG and MEG were 35.84 ± 1.75 μg/ml and 83.14 ± 1.26 μg/ml, respectively. The best hypoglycemic activity was observed in the TAG group. The group given TAG and high glucose had lower blood glucose (127 mg/dl) compared to the group only given high glucose (178 mg/dl). These results indicated that TAG had a better potential for antidiabetic activities compared to MEG, and it can be proposed for further investigations as a potential antidiabetic agent.